Composite clusters: Co5.7Ni2.3W12O42(OH)4@fluoro-graphdiyne as a stable electrode for sustained electrochemical oxygen evolution under high current conditions. (20th September 2021) - Sun, Hao; Xu, Xiaomei; Jing, Chaojun; Shang, Wenhui; Wang, Yongchun; Zeng, Muling; Jia, Zhiyu
Abstract : A composite cluster [Co5.7 Ni2.3 W12 O42 (OH)4 @FGDY] exhibited high performance for the electrochemical oxygen evolution reaction with low potentials at high current density and long stability. Abstract : A composite cluster composed of Dexter–Silverton structure polyoxometalates (POMs) and porous fluoro-graphdiyne (FGDY) was synthesized and applied for the electrochemical oxygen evolution reaction (OER). Compared with the original POMs and FGDY, the composite cluster Co5.7 Ni2.3 W12 O42 (OH)4 @FGDY demonstrates superior performance and stability for the electrochemical OER. The composite cluster exhibited high performance for the OER with low potentials and a small Tafel slope. High catalytic activity could be obtained at a high current density. Co5.7 Ni2.3 W12 O42 (OH)4 @FGDY exhibits excellent catalytic performance and long stability due to its strong electron-transfer ability in the system, higher conductivity, and structural advantage of pores in FGDY. This would open access and guide us to synthesize novel composite clusters based on polyoxometalates and graphdiyne.